Fighting the Pipe: Neoliberal Governance and Barriers to Effective Community Participation in Energy Infrastructure Planning. (April 2013) - Groves, Christopher; Munday, Max; Yakovleva, Natalia
Development of effective participatory mechanisms within infrastructure planning governance has been dependent on how far the outputs of participatory processes have an impact upon strategic policy priorities. However, neoliberal modes of governance are characterised by 'recentralisation' within arms-length regulatory bodies and private corporations. Tensions between participatory governance and recentralisation are exemplified by the relationship between energy privatisation and energy infrastructure planning. With this study we examine these tensions using a case study of a critical infrastructure project in the UK, the South Wales Gas Pipeline. Findings confirm arguments in the literature that siting conflicts often centre on policy issues as much as local concerns. The study reveals that the neoliberal recentralisation of some governance functions exacerbates such conflicts. We argue that, although new efforts to secure effective participation in neoliberal regimes are necessary, they will face obstacles in the form of risk-based governance structures, as exemplified by the privatised energy sector.